2021
DOI: 10.1038/s41598-021-81131-9
|View full text |Cite
|
Sign up to set email alerts
|

Pteropods make thinner shells in the upwelling region of the California Current Ecosystem

Abstract: Shelled pteropods are widely regarded as bioindicators for ocean acidification, because their fragile aragonite shells are susceptible to increasing ocean acidity. While short-term incubations have demonstrated that pteropod calcification is negatively impacted by ocean acidification, we know little about net calcification in response to varying ocean conditions in natural populations. Here, we examine in situ calcification of Limacina helicina pteropods collected from the California Current Ecosystem, a coast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 63 publications
1
41
0
Order By: Relevance
“…Measuring calcification is a clear choice because of its known sensitivity to low values of ar and the relative wealth of relevant laboratory studies concerning the ability of organisms to create calcium carbonate structures under OA conditions. Recent research studying in situ impacts on calcification found reduced calcification in pteropods collected in the California Current Ecosystem (Mekkes et al, 2021) and severe dissolution in pteropods in our study area (Bednaršek et al, 2020b). Importantly, some measures of calcification can be made on preserved samples, potentially alleviating constraints of some monitoring programs.…”
Section: Discussionmentioning
confidence: 78%
“…Measuring calcification is a clear choice because of its known sensitivity to low values of ar and the relative wealth of relevant laboratory studies concerning the ability of organisms to create calcium carbonate structures under OA conditions. Recent research studying in situ impacts on calcification found reduced calcification in pteropods collected in the California Current Ecosystem (Mekkes et al, 2021) and severe dissolution in pteropods in our study area (Bednaršek et al, 2020b). Importantly, some measures of calcification can be made on preserved samples, potentially alleviating constraints of some monitoring programs.…”
Section: Discussionmentioning
confidence: 78%
“…Indeed, because the ocean is absorbing an increasing amount of human-released CO 2 , seawater is acidifying [22,23]. Previous studies have found that a decrease of pH in the ocean reduces the calcification rate of marine organisms which use CaCO 3 to build their skeleton or shells [24,25]. Meanwhile, freshening of the surface seawater, and the consequence of the capping effect, may cause anoxic bottom water inside the harbor [26].…”
Section: Quality Of the Distilled Or Ro Watermentioning
confidence: 99%
“…An increase in atlantid shell extension from ambient to 2050 conditions may indicate a stress response to grow to a larger size as quickly as possible under increasing OA. It has been shown that some calcifying organisms are able to increase the rates of BP, such as metabolism and calcification, in response to low pH in order to compensate for the negative effects that increased acidity can cause, such as impaired calcification [85,86]. However, this often comes at a cost to overall fitness [85] and such increased rates cannot be sustained in the long term.…”
Section: A Complex Response To Oamentioning
confidence: 99%